Mechanical and corrosion properties of gas and water atomized laser-powder bed fusion fabricated 25Cr7Ni stainless steel. (January 2022) - Arumugham Akilan, Arulselvan; Nath, Subrata D.; Enneti, Ravi K.; Gupta, Gautam; Atre, Sundar V.
Abstract: Several components fabricated from 25Cr7Ni stainless steel are widely used in industry owing to its beneficial combination of high strength and superior corrosion resistance. There are very few studies reported in the literature on the laser-powder bed fusion (L-PBF) fabricated properties of 25Cr7Ni stainless steel. The current study is focused on understanding the effect of powder attributes and chemical composition on the properties of L-PBF processed 25Cr7Ni stainless steel. L-PBF fabricated samples made from gas and water atomized 25Cr7Ni powders were evaluated in the present study for densification, mechanical and corrosion properties. The L-PBF samples processed from gas atomized powders displayed higher densification, tensile strength and superior corrosion resistance compared to samples made from water atomized powders. The superior corrosion resistance of L-PBF samples made from gas atomized powders is attributed to the presence of austenite phase in microstructure. The corrosion resistance of L-PBF gas atomized powder samples were comparable to the wrought-annealed 25Cr7Ni stainless steel.